Implementation of the food safety management system - Holoskov, Konstantin; Kuzmin, Oleg; Mikhailov, Bohdan (My University, 2023)
The abstracts of the report analyze the implementation of the HACCP system, which supports the reputation of the manufacturer of a high-quality and safe food product, facilitates inspection by regulatory bodies and promotes international trade, increasing the confidence of buyers. У тезах доповіді проаналізовано впровадження системи HACCP, що підтримує репутацію виробника якісного та безпечного харчового продукту, полегшує перевірку контролюючими органами та сприяє міжнародній торгівлі, підвищуючи довіру покупців.
Keywords: HACCP; безпека кінцевого продукту; харчовий ланцюг; законодавство ЄС; safety of the final product; food chain; EU legislation; кафедра технології ресторанної і аюрведичної продукції